BETWEEN LEGALITY AND LEGITIMACY IN THE PROCEDURAL JUSTICE OF THE ENACTMENT OF LAW NO. 17 OF 2023 ON HEALTH - Hertanto, Yudhi; Sapsudin, Asep (Law Faculty of Universitas Bandar Lampung, 2026)
This article examines the tension between legality and legitimacy within the procedural justice framework of Indonesia’s Law No. 17 of 2023 on Health. While the law formally satisfies the positivistic criteria of legality as outlined in statutory drafting guidelines, its legislative process raised substantial concerns regarding transparency, participation, and deliberative inclusiveness. These issues highlight the broader philosophical problem of whether legal validity based solely on procedural formality is sufficient to constitute legitimate lawmaking in a democratic state governed by the rule of law. Using theoretical perspectives from Habermas, Fuller, and Rawls, this study analyzes the degree to which the formation of the Health Law reflects or departs from the ideals of procedural justice. Habermasian discourse theory underscores the importance of communicative participation and rational–public deliberation, both of which appear limited in the law’s formation. Fuller’s principles of internal morality reveal inconsistencies related to clarity, openness, and procedural integrity. Meanwhile, Rawls’s notion of fairness emphasizes the need for equitable inclusion of affected stakeholders, particularly healthcare professionals and the wider public. The findings show that although the law may be legally valid, its legitimacy remains contested due to insufficient adherence to philosophical standards of just procedure. This paper concludes that bridging legality and legitimacy requires strengthening deliberative mechanisms, enhancing participatory routes, and reaffirming moral–procedural principles in legislative processes.